Effective Corporate Taxation, Tax Incidence and Tax Reforms: Evidence from OECD Countries - Salvador Barrios; Gaëtan J.A. Nicodème; Antonio Jesus Sanchez Fuentes (Center for Economic Studies and ifo Institute (CESifo), 2014)
The present study provides estimates of the Effective Marginal Tax Rates (EMTRs) for a sample of 17 OECD countries and 11 manufacturing sectors in a single framework encompassing capital, labour and energy taxes. Our cross-country/cross-sector approach allows us comparing the incentives provided by the tax systems and gauging the effects of tax changes taking explicitly into account the possible substitution between factors as well as their tax incidence. Our results suggest that the OECD tax systems provide different incentives for manufacturing activity across countries and that tax systems are relatively neutral with respect to the sectoral composition of manufacturing activities. The impact of potential tax increases on firms activity is found to be most attenuated when shifted towards consumers and/or employees rather than energy consumption and/or capital investors. These results are robust to alternative hypotheses regarding the tax incidence parameters, elasticity of substitution between factors and mark-up on final prices. In addition, policy strategies favouring tax increases on energy consumption and lowering taxes on labour can substantially reduce the EMTRs and thus yield substantial efficiency gains for firms. These reforms should in some instances be ambitious enough to produce desired effects on firms' EMTRs, however.
Keywords: H20; H22; H24; H25; 330; taxation; tax incidence; effective taxation